Zebrafish cerebrospinal fluid mediates cell survival through a retinoid signaling pathway. Issue 1 (8th June 2015) - Chang, Jessica T.; Lehtinen, Maria K.; Sive, Hazel
ABSTRACT: Cerebrospinal fluid (CSF) includes conserved factors whose function is largely unexplored. To assess the role of CSF during embryonic development, CSF was repeatedly drained from embryonic zebrafish brain ventricles soon after their inflation. Removal of CSF increased cell death in the diencephalon, indicating a survival function. Factors within the CSF are required for neuroepithelial cell survival as injected mouse CSF but not artificial CSF could prevent cell death after CSF depletion. Mass spectrometry analysis of the CSF identified retinol binding protein 4 (Rbp4), which transports retinol, the precursor to retinoic acid (RA). Consistent with a role for Rbp4 in cell survival, inhibition of Rbp4 or RA synthesis increased neuroepithelial cell death. Conversely, ventricle injection of exogenous human RBP4 plus retinol, or RA alone prevented cell death after CSF depletion. Zebrafish rbp4 is highly expressed in the yolk syncytial layer, suggesting Rbp4 protein and retinol/RA precursors can be transported into the CSF from the yolk. In accord with this suggestion, injection of human RBP4 protein into the yolk prevents neuroepithelial cell death in rbp4 loss‐of‐function embryos. Together, these data support the model that Rbp4 and RA precursors are present within the CSF and used for synthesis of RA, which promotes embryonic neuroepithelial survival. © 2015 Wiley Periodicals, Inc. Develop Neurobiol 76: 75–92, 2016